Do 'efémero' ao 'sistema de informação': a preservação na era digital - Maria Manuela Gomes de Azevedo Pinto (2005)
The main purpose of this article is to give a synthetic overview of the information collected in the research project that we have just started regarding management and preservation of digital information, which is one of the key challenges facing organizations at this time, focusing on the projects already developed, in course, or planned. We pretend not only to give a perception of the national and international developed work, but also promote new projects and reinforce the necessary theoretical and scientific reflection which is the basis of a «praxis» more and more sustained in the cooperation, interdisciplinary, and, necessarily, in the assumption of the social information system, object of the Information Science.